Positive electrode active material, and electrochemical device and electronic device including said positive electrode active material
By optimizing the Al/Mn molar ratio distribution in lithium manganate particles, the Mn elution issue is mitigated, leading to improved cycle and storage characteristics in lithium-ion batteries.
Patent Information
- Application Number
- JP2024541688
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2022-01-29
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2042-01-29
AI Technical Summary
The Mn 2+ elution from lithium manganate in positive electrode active materials leads to the deterioration of lithium-ion batteries' cycle and storage characteristics due to the destruction of the solid electrolyte interface (SEI), reducing the specific capacity and overall performance.
A positive electrode active material with a specific Al/Mn molar ratio distribution across different regions of the particle surface and interior is developed, concentrating Al on the surface to minimize Mn elution while maintaining high specific capacity.
This approach enhances the cycle and storage characteristics of lithium-ion batteries by reducing Mn elution and preserving the positive electrode's specific capacity, thereby improving the overall performance of the electrochemical device.
Smart Images

Figure 2025501390000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to the field of electrochemistry, and in particular to positive electrode active materials, electrochemical devices and electronic devices that include the positive electrode active materials. [Background technology]
[0002] Lithium-ion batteries have the advantages of high energy density, long cycle life, no memory effect, etc., and are therefore widely used in the fields of devices such as wearable devices, smartphones, unmanned aerial vehicles, electric vehicles, and large-scale energy storage. Lithium-ion batteries have become the new green chemical power source with the most potential for development in the world at present, but at the same time, the requirements for the comprehensive properties of lithium-ion batteries are becoming higher.
[0003] The positive electrode active material in lithium-ion batteries is an important parameter that affects the performance of lithium-ion batteries. Here, the positive electrode active material lithium manganese oxide is widely used in lithium-ion batteries, but the Mn in lithium manganese oxide 3+ Disproportionation reaction is likely to occur, and Mn 2+ This causes the dissolution of Mn, which then migrates to the negative electrode through the electrolyte, destroying the solid electrolyte interface (SEI), causing a loss of active lithium, and deteriorating the cycle characteristics of the lithium-ion battery. 2+ While improving the dissolution of the positive electrode, this often results in a decrease in the specific capacity of the positive electrode and a deterioration in the cycle characteristics or storage characteristics of the electrochemical device, resulting in a decrease in the overall characteristics of the electrochemical device. Summary of the Invention
[0004] An object of the present invention is to provide a positive electrode active material capable of improving the overall characteristics of an electrochemical device, and an electrochemical device and an electronic device each including the positive electrode active material.
[0005] The first aspect of the present invention provides a cathode active material containing Mn and Al elements, the cathode active material particles including a first region close to the surface of the cathode active material particles and a second region away from the surface of the cathode active material particles, and when the molar ratio of Al / Mn in the first region is a1 and the molar ratio of Al / Mn in the second region is a2, a1 and a2 satisfy 1.1≦a1 / a2≦100, preferably 5≦a1 / a2≦90. The value of a1 / a2 may be 1.1, 5, 10, 20, 30, 40, 50, 60, 70, 80, 90, or 100, or any range of the above values. Here, the first region refers to a portion dissolved after washing the cathode active material particles with 2.4 mol / L sulfuric acid for 6 hours, and the second region refers to a portion not dissolved after washing the cathode active material particles with 2.4 mol / L sulfuric acid for 6 hours.
[0006] The present inventors have discovered that by adjusting the ratio a1 / a2 between the molar ratio a1 of Al / Mn in the first region and the molar ratio a2 of Al / Mn in the second region within the above range, Al in the positive electrode active material is concentrated in a region close to the surface of the positive electrode active material, thereby not only effectively improving the manganese elution phenomenon of the positive electrode and improving the cycle characteristics and storage characteristics of the electrochemical device, but also simultaneously reducing the total Al content in the positive electrode active material, thereby maintaining a high specific capacity of the positive electrode, and improving the overall characteristics of the electrochemical device.
[0007] Specifically, when the value of a1 / a2 is too small (e.g., less than 1.1), the molar ratios of Al / Mn in the first and second regions are almost the same, or the molar ratio of Al / Mn in the first region is smaller than that in the second region, i.e., Al in the positive electrode active material is mainly concentrated inside the positive electrode active material particles. Therefore, the manganese elution phenomenon of the positive electrode is hardly improved, which is disadvantageous for improving the cycle characteristics and storage characteristics of the electrochemical device. As the value of a1 / a2 gradually increases, Al in the obtained positive electrode active material is mainly concentrated on the surface of the positive electrode active material particles. Therefore, it can contribute to maintaining the specific capacity of the positive electrode while improving the manganese elution of the positive electrode. However, when the value of a1 / a2 is too large (e.g., more than 100), i.e., when the molar ratio a1 of Al / Mn in the first region is too large, the total content of Al in the positive electrode active material increases, and the specific capacity of the positive electrode decreases. Adjusting the value of a1 / a2 within the above range contributes to simultaneously improving the cycle characteristics and storage characteristics of the electrochemical device, and allows the positive electrode to maintain a high specific capacity, thereby improving the overall characteristics of the electrochemical device.
[0008] In some embodiments of the present invention, the mass percentage of Al in the first region is 0.01% to 0.5% relative to the mass of the positive electrode active material. For example, the mass percentage of Al in the first region can be 0.01%, 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, or 0.5%, or any range of the above values. By adjusting the mass percentage of Al in the first region within the above range, it is possible to improve the manganese elution of the positive electrode and at the same time contribute to maintaining a high specific capacity of the positive electrode, thereby improving the overall characteristics of the electrochemical device.
[0009] In some embodiments of the present invention, the positive electrode active material is selected from lithium manganese oxides (LMOs) containing the element Al.
[0010] In some embodiments of the present invention, the molar ratio a1 of Al / Mn in the first region is 1%-30%, preferably 5%-30%, and / or the molar ratio a2 of Al / Mn in the second region is 0.05%-5%. For example, the molar ratio a1 of Al / Mn in the first region can be 1%, 5%, 10%, 15%, 20%, 25%, or 30%, or any range of the above values. For example, the molar ratio a2 of Al / Mn in the second region can be 0.05%, 0.1%, 0.2%, 0.3%, 0.4%, or 0.5%, or any range of the above values.
[0011] If the molar ratio a1 of Al / Mn in the first region is too small (e.g., less than 1%), not only is it impossible to improve the elution of manganese from the positive electrode and improve the cycle characteristics and storage characteristics of the electrochemical device, but the introduction of Al also reduces the specific capacity of the positive electrode to a certain extent. If the molar ratio a1 of Al / Mn in the first region is too large (e.g., more than 30%), the total content of Al in the positive electrode active material increases, and the specific capacity of the positive electrode decreases. If the molar ratio a2 of Al / Mn in the second region is too small (e.g., less than 0.05%) or too large (e.g., more than 0.5%), it is disadvantageous to improving the cycle characteristics and storage characteristics of the electrochemical device. By adjusting the molar ratio a1 of Al / Mn in the first region and / or the molar ratio a2 of Al / Mn in the second region within the range of the present invention, it is possible to simultaneously improve the cycle characteristics and storage characteristics of the electrochemical device, and maintain a high specific capacity of the positive electrode, thereby contributing to improving the overall characteristics of the electrochemical device.
[0012] In some embodiments of the present invention, the positive electrode active material is (a) the molar ratio of Al / Mn in the positive electrode active material is 0.1% to 10%, preferably 2% to 10%, (b) Mn element is Mn 3+ and Mn 4+ In the second region, Mn 3+ / Mn 4+ The mole ratio of Mn in the first region 3+ / Mn 4+When the molar ratio of the above is e, e is 0.8 to 0.95; (c) the positive electrode active material further contains Li, and when a molar ratio of Li / Mn in the first region is b1 and a molar ratio of Li / Mn in the second region is b2, b1 and b2 satisfy 1≦b1 / b2≦2, preferably 1.1≦b1 / b2≦2; At least one of the conditions above is satisfied. For example, the molar ratio of Al / Mn in the positive electrode active material can be 0.1%, 0.5%, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10%, or can be in any range of the above values. For example, the value of e can be 0.8, 0.83, 0.85, 0.87, 0.9, 0.92, or 0.95, or can be in any range of the above values. For example, the value of b1 / b2 can be 1, 1.1, 1.2, 1.4, 1.6, 1.8, or 2, or can be in any range of the above values.
[0013] If the molar ratio of Al / Mn in the positive electrode active material is too small (e.g., less than 0.1%), the manganese elution phenomenon in the positive electrode is hardly improved, and the cycle characteristics and storage characteristics of the electrochemical device are hardly improved. If the molar ratio of Al / Mn in the positive electrode active material is too large (e.g., more than 10%), the specific capacity of the positive electrode decreases. By adjusting the molar ratio of Al / Mn in the positive electrode active material to within the above range, it contributes to improving the cycle characteristics and storage characteristics of the electrochemical device, and allows the positive electrode to maintain a high specific capacity, thereby improving the overall characteristics of the electrochemical device.
[0014] In some embodiments of the present invention, Al is 0.005% to 0.1% by mass percentage relative to the mass of the positive electrode active material. For example, Al in the positive electrode active material may be 0.005%, 0.01%, 0.02%, 0.05%, 0.08%, or 0.1% by mass percentage, or any range of the above values. By adjusting the mass percentage of Al in the positive electrode active material to within the above range, it is possible to improve the manganese elution of the positive electrode and at the same time contribute to maintaining a high specific capacity of the positive electrode, thereby improving the overall characteristics of the electrochemical device.
[0015] In some embodiments of the present invention, the mass percentage of Mn is 1.0% to 1.2% relative to the mass of the positive electrode active material. By adjusting the mass percentage of Mn in the positive electrode active material to fall within the above range, manganese elution from the positive electrode is improved, and at the same time, a high specific capacity of the positive electrode is maintained, thereby improving the overall characteristics of the electrochemical device.
[0016] Mn in the second region 3+ / Mn 4+ The mole ratio of Mn in the first region 3+ / Mn 4+ When the molar ratio e of the first region is within the range of the present invention, it contributes to improving the manganese elution phenomenon, and improves the cycle characteristics and storage characteristics of the electrochemical device. 3+ / Mn 4+ and the molar ratio of Mn in the second region 3+ / Mn 4+ The molar ratio of Mn in the first region is not particularly limited as long as it satisfies the range of e. For example, 3+ / Mn 4+ The molar ratio of Mn in the second region is 15% to 55%. 3+ / Mn 4+ The molar ratio of is 30% to 70%.
[0017] By setting the ratio b1 / b2 between the molar ratio b1 of Li / Mn in the first region and the molar ratio b2 of Li / Mn in the second region within the above range, the molar ratio b1 of Li / Mn in the first region is larger than the molar ratio b2 of Li / Mn in the second region, which can contribute to improving the cycle characteristics of the electrochemical device and maintaining a high specific capacity of the positive electrode.
[0018] In some embodiments of the present invention, the Li / Mn molar ratio b1 in the first region is 58%-98%, and the Li / Mn molar ratio b2 in the second region is 55%-60%. For example, the Li / Mn molar ratio b1 in the first region can be 58%, 60%, 65%, 70%, 75%, 80%, 85%, 90%, 95%, or 98%, or any range of the above values. The Li / Mn molar ratio b2 in the second region can be 55%, 55.5%, 56%, 56.5%, 57%, 57.5%, 58%, 58.5%, 59%, 59.5%, or 60%, or any range of the above values. Adjusting the Li / Mn molar ratio b1 in the first region and the Li / Mn molar ratio b2 in the second region within the above ranges can contribute to improving the cycle characteristics of the electrochemical device and maintaining a high specific capacity of the positive electrode.
[0019] In some embodiments of the present invention, the positive electrode active material further comprises an M1 element, the M1 element comprising at least one of Ni, Co, Nb, Mo, V, W, Zr, Mg, Ti, La, Y, and B elements, and the positive electrode active material comprises (d) the molar ratio of M1 / Mn is 0.1% to 5%; (e) the molar ratio of Al / M1 is 1 to 10; For example, the molar ratio of M1 / Mn can be 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, or 5%, or any range of values therein. For example, the molar ratio of Al / M1 can be 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5, 5, 6, 7, 8, 9, or 10, or any range of values therein.
[0020] When the positive electrode active material contains the M1 element and the molar ratio of M1 / Mn and / or the molar ratio of Al / M1 is within the above range, the storage characteristics of the electrochemical device can be improved and the specific capacity of the positive electrode can be maintained high.
[0021] In some embodiments of the present invention, the positive electrode active material further includes an M2 element, the M2 element including F and / or S, and the M2 element is present in a mass percentage of 0.1% to 2% relative to the mass of the positive electrode active material. For example, the M2 element may be present in a mass percentage of 0.1%, 0.3%, 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, or 2%, or in any range of the above values.
[0022] If the mass percentage of the M2 element is too low (e.g., less than 0.1%), the characteristics of the electrochemical device are hardly improved. As the mass percentage of the M2 element increases, it can contribute to improving the specific capacity of the positive electrode. However, if the mass percentage of the M2 element is too high (e.g., more than 2%), the cycle characteristics of the electrochemical device deteriorate. By adjusting the mass percentage of the M2 element within the above range, it can improve the cycle characteristics of the electrochemical device and contribute to maintaining a high specific capacity of the positive electrode.
[0023] In some embodiments of the present invention, the M2 element includes an F element, and when the molar ratio of F / Mn in the first region is d1 and the molar ratio of F / Mn in the second region is d2, d1 and d2 satisfy 3≦d1 / d2≦50, preferably 3≦d1 / d2≦25. For example, the value of d1 / d2 can be 3, 5, 10, 15, 20, 25, 30, 35, 40, 45, or 50, or any range consisting of the above numerical values.
[0024] By introducing the M2 element into the positive electrode active material, the cycle characteristics of the electrochemical device can be improved, but an excessive amount of the M2 element affects the specific capacity of the positive electrode. By adjusting the value of d1 / d2 within the range of the present invention and making the F / Mn molar ratio d1 in the first region larger than the F / Mn molar ratio d2 in the second region, that is, by concentrating the F element in the surface region of the positive electrode active material, the cycle characteristics of the electrochemical device can be improved and the specific capacity of the positive electrode can be maintained high. In the present invention, the F / Mn molar ratio d1 in the first region and the F / Mn molar ratio d2 in the second region are not particularly limited as long as they satisfy the range of d1 / d2. For example, the F / Mn molar ratio d1 in the first region is 1% to 2.5%, and the F / Mn molar ratio d2 in the second region is 0.05% to 0.5%.
[0025] In some embodiments of the present invention, the positive electrode active material further includes Nb, where c1 is a molar ratio of Nb / Mn in the first region and c2 is a molar ratio of Nb / Mn in the second region, and c2 satisfies 3≦c1 / c2≦50. For example, the value of c1 / c2 can be 3, 10, 15, 20, 25, 30, 35, 40, or 45, or any range of the above numerical values.
[0026] Introducing Nb element into the positive electrode active material and setting the value of c1 / c2 within the above range can contribute to improving the cycle characteristics of the electrochemical device. In the present invention, the molar ratio c1 of Nb / Mn in the first region and the molar ratio c2 of Nb / Mn in the second region are not particularly limited as long as they satisfy the range of c1 / c2. For example, the molar ratio c1 of Nb / Mn in the first region is 1% to 5%, and the molar ratio c2 of Nb / Mn in the second region is 0.1% to 0.8%.
[0027] In some embodiments of the present invention, the positive electrode active material has a Dv99 of 15 μm to 50 μm, preferably 25 μm to 35 μm, and the particle size of the positive electrode active material is (i) Dv90 and Dv99 satisfy 5 μm≦Dv90≦30 μm, 5 μm≦Dv99-Dv90≦21 μm, and preferably 8 μm≦Dv99-Dv90≦12 μm; (ii) Dv10, Dv50 and Dv99 satisfy 2 μm≦Dv10≦10 μm, 1≦(Dv99-Dv10) / Dv50≦4, preferably 4 μm≦Dv10≦7 μm, 2≦(Dv99-Dv10) / Dv50≦3; At least one of the conditions is met.
[0028] For example, the Dv99 of the positive electrode active material may be 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 45 μm, or 50 μm, or any range of the above values. For example, the Dv90 of the positive electrode active material may be 5 μm, 8 μm, 10 μm, 13 μm, 15 μm, 18 μm, 20 μm, 23 μm, 25 μm, 28 μm, or 30 μm, or any range of the above values. The value of Dv99-Dv90 may be 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, 18 μm, 20 μm, or 21 μm, or any range of the above values. For example, the Dv10 of the positive electrode active material can be 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, or 10 μm, or any range between the above values. The value of (Dv99-Dv10) / Dv50 can be 1, 1.5, 2, 2.5, 3, 3.5, or 4, or any range between the above values.
[0029] Adjusting the Dv99, Dv90 and Dv99-Dv90 values of the positive electrode active material within the above ranges, or adjusting the Dv99, Dv10 and (Dv99-Dv10) / Dv50 values of the positive electrode active material within the above ranges, or adjusting the Dv99, Dv90, Dv99-Dv90 values, Dv10 and (Dv99-Dv10) / Dv50 values of the positive electrode active material within the above ranges, can all contribute to improving the overall characteristics of the electrochemical device.
[0030] In the present invention, the method for preparing the positive electrode active material is not particularly limited as long as the object of the present invention can be achieved. For example, the method for preparing the positive electrode active material is as follows: mixing the raw materials and performing a first firing at a temperature T1 for a firing time t1 to obtain an intermediate product; Next, adding an intermediate raw material, mixing with the intermediate product, and performing a second firing at a temperature T2 with a firing time t2 to obtain a positive electrode active material; These may include, but are not limited to:
[0031] In the present invention, the temperature T1 and firing time t1 of the first firing, and the temperature T2 and firing time t2 of the second firing are not particularly limited as long as they achieve the object of the present invention. For example, T1 is 800°C to 900°C, t1 is 35 hours to 45 hours, T2 is 450°C to 600°C, and t2 is 5 hours to 15 hours.
[0032] In the present invention, the raw materials and intermediate raw materials are not particularly limited as long as they achieve the object of the present invention. For example, the raw materials and intermediate raw materials may each independently contain at least one of MnO2, Li2CO3, and Al2O3, but are not limited thereto.
[0033] The calcination temperature and calcination time generally affect the distribution of elements in the positive electrode active material in the positive electrode active material particles, for example, lowering the calcination temperature and / or shortening the calcination time causes the elements to be distributed in regions closer to the surface of the positive electrode active material particles, such as the first region of the present invention, whereas increasing the calcination temperature and / or extending the calcination time causes the elements to be distributed in regions farther from the surface of the positive electrode active material particles, such as the second region of the present invention.
[0034] In the present invention, the method of introducing element M1 into the positive electrode active material is not particularly limited as long as it achieves the object of the present invention, and for example, a compound containing M1 can be added during preparation of the positive electrode active material. In the present invention, the compound containing M1 is not particularly limited as long as it achieves the object of the present invention, and for example, it can include at least one of MgO, nickel acetate, TiO2, ZrO2, Nb2O5, MoO3, V2O5, WO3 and Y2O3, but is not limited thereto.
[0035] In the present invention, the method of introducing element M2 into the positive electrode active material is not particularly limited as long as it achieves the object of the present invention, and for example, a compound containing M2 can be added during preparation of the positive electrode active material. In the present invention, the compound containing M2 is not particularly limited as long as it achieves the object of the present invention, and for example, it can include at least one of MnS and LiF, but is not limited thereto.
[0036] A second aspect of the present invention provides an electrochemical device including a positive electrode, a negative electrode, and an electrolyte, the positive electrode including the positive electrode active material according to any one of the embodiments of the present invention, the positive electrode including a positive electrode material layer and a positive electrode current collector, the positive electrode material layer including a first positive electrode material layer and a second positive electrode material layer, the first positive electrode material layer being located between the second positive electrode material layer and the positive electrode current collector, and the Mn element content in the first positive electrode material layer being greater than the Mn element content in the second positive electrode material layer. The fact that the Mn element content in the first positive electrode material layer is greater than the Mn element content in the second positive electrode material layer contributes to reducing the manganese elution phenomenon of the positive electrode, and improves the cycle characteristics and storage characteristics of the electrochemical device.
[0037] In some embodiments of the present invention, the electrolyte is (iii) the electrolyte contains a chain carbonate, the chain carbonate is present in a mass percentage of 20% to 60%, and the chain carbonate contains at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC) and ethyl methyl carbonate (EMC); (iv) the electrolytic solution contains a benzene-containing compound, the benzene-containing compound is present in a mass percentage of 0.01% to 5%, preferably 0.01% to 3%, and more preferably 1% to 3%, and the benzene-containing compound contains at least one of biphenyl (BP), fluorobenzene (FP), and cyclohexylbenzene (CHB); (v) the electrolyte contains polystyrene (PS), and the polystyrene content is 0.01% to 5%, preferably 0.01% to 3%, by mass percentage; At least one of the conditions is met.
[0038] For example, the linear carbonate may be 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, or 60% by mass, or any range of the above values. For example, the benzene-containing compound may be 0.01%, 0.05%, 0.1%, 1%, 2%, 3%, 4%, or 5% by mass, or any range of the above values. For example, the polystyrene may be 0.01%, 0.05%, 0.1%, 1%, 2%, 3%, 4%, 5%, or any range of the above values by mass. By optionally adding at least one of the linear carbonate, the benzene-containing compound, and the polystyrene to the electrolyte and setting the mass percentage within the above range, it contributes to forming a synergistic effect between the positive electrode active material and the electrolyte, and improves the cycle characteristics and storage characteristics of the electrochemical device.
[0039] In some embodiments of the present invention, the negative electrode comprises a negative electrode material layer, the negative electrode material layer comprises a negative electrode active material, the negative electrode active material comprises at least one of natural graphite, artificial graphite, and hard carbon, and the electrochemical device comprises: (vi) Dv10 of the negative electrode active material satisfies 2 μm≦Dv10≦10 μm, preferably 3 μm≦Dv10≦8 μm; (vii) Dv90 and Dv99 of the negative electrode active material satisfy 5 μm≦Dv90≦20 μm, 5 μm≦Dv99−Dv90≦25 μm, preferably 5 μm≦Dv90≦15 μm, 5 μm≦Dv99−Dv90≦10 μm; (viii) the orientation index (OI) of the negative electrode active material is 5 to 30, preferably 8 to 20; (ix) the degree of graphitization of the negative electrode active material is 92% to 96%, preferably 93% to 95%; At least one of the conditions is met.
[0040] For example, the Dv10 of the negative electrode active material can be 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, or 10 μm, or in any range of the above values. For example, the Dv90 of the negative electrode active material can be 5 μm, 8 μm, 10 μm, 13 μm, 15 μm, 18 μm, or 20 μm, or in any range of the above values. The value of Dv99-Dv90 can be 5 μm, 8 μm, 10 μm, 13 μm, 15 μm, 18 μm, 20 μm, 23 μm, or 25 μm, or in any range of the above values. For example, the value of OI of the negative electrode active material can be 5, 8, 10, 13, 15, 18, 20, 23, 25, 28, or 30, or in any range of the above values. For example, the degree of graphitization of the negative electrode active material can be 92%, 93%, 94%, 95%, or 96%, or any range between the above values.
[0041] By setting at least one of the Dv10 of the negative electrode active material, the Dv10, Dv90 and Dv99-Dv90 values of the negative electrode active material, the OI value of the negative electrode active material, and the graphitization degree of the negative electrode active material within the range of the present invention, it is possible to contribute to the formation of a synergistic effect between the negative electrode active material, the positive electrode active material, and the electrolyte, and to contribute to improving the cycle characteristics and storage characteristics of the electrochemical device.
[0042] In some embodiments of the present invention, the electrochemical device includes a separator, and the separator has a heat generation onset temperature measured by differential scanning calorimetry (DSC) of 138°C to 145°C, preferably 141°C to 143°C, more preferably 141°C to 142°C. For example, the separator has a heat generation onset temperature measured by differential scanning calorimetry of 138°C, 139°C, 140°C, 141°C, 142°C, 143°C, 144°C, or 145°C, or any range of the above values. Adjusting the separator's heat generation onset temperature measured by DSC within the range of the present invention contributes to forming a synergistic effect between the separator and the negative electrode material, the positive electrode active material, and the electrolyte, and can contribute to improving the cycle characteristics and storage characteristics of the electrochemical device.
[0043] In the present invention, the molar ratio of the different elements in the positive electrode active material is calculated from the contents of the different elements obtained by disassembling an electrochemical device containing the positive electrode active material at a 0% state of charge to obtain a positive electrode and then measuring the contents of the different elements.
[0044] In the present invention, the positive electrode current collector is not particularly limited as long as it achieves the object of the present invention, and may include, but is not limited to, for example, aluminum foil, aluminum alloy foil, composite current collector, etc. In the present invention, the thickness of the positive electrode current collector is not particularly limited as long as it achieves the object of the present invention, and is, for example, 8 μm to 12 μm.
[0045] In the present invention, the positive electrode material layer includes the positive electrode active material in any of the above embodiments of the present invention, and the positive electrode material layer can further include a binder. In the present invention, the binder is not particularly limited as long as it achieves the object of the present invention, and can include at least one of, for example, polyacrylic acid, sodium polyacrylate, potassium polyacrylate, lithium polyacrylate, polyimide, polyvinyl alcohol, carboxymethyl cellulose, sodium carboxymethyl cellulose, polyimide, polyamide imide, styrene butadiene rubber, and polyvinylidene fluoride, but is not limited thereto.
[0046] In the present invention, the positive electrode material layer may further include a conductive agent. In the present invention, the conductive agent may be any material that can achieve the object of the present invention, and is not particularly limited. For example, the conductive agent may include at least one of conductive carbon black (Super P), carbon nanotubes (CNTs), carbon fibers, flake graphite, Ketjen black, graphene, metal materials, and conductive polymers, but is not limited thereto. The carbon nanotubes may include, but are not limited to, single-walled carbon nanotubes and / or multi-walled carbon nanotubes. The carbon fibers may include, but are not limited to, vapor grown carbon fibers (VGCF) and / or nano carbon fibers. The metal materials may include, but are not limited to, metal powders and / or metal fibers, and specifically, the metal may include, but is not limited to, at least one of copper, nickel, aluminum, and silver. The conductive polymer may include, but is not limited to, at least one of polyphenylene derivatives, polyanilines, polythiophenes, polyacetylenes, and polypyrroles.
[0047] Optionally, the positive electrode may further include a conductive layer, and the conductive layer is located between the positive electrode current collector and the positive electrode material layer. In the present invention, the composition of the conductive layer is not particularly limited, and may be a conductive layer commonly used in the field, for example, it may include the conductive agent and the binder, but is not limited thereto.
[0048] In the present invention, the negative electrode may include a negative electrode current collector, and the negative electrode current collector of the present invention may be any material that achieves the object of the present invention, and may include, but is not limited to, copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, or a composite current collector. In the present invention, the thickness of the negative electrode current collector may be any material that achieves the object of the present invention, and may be, for example, 4 μm to 12 μm. In the present invention, the negative electrode material layer may be provided on one surface in the thickness direction of the negative electrode current collector, or may be provided on both surfaces in the thickness direction of the negative electrode current collector. The above "surface" may be the entire region of the negative electrode current collector, or may be a part of the region of the negative electrode current collector, and the present invention may be any material that achieves the object of the present invention, and is not particularly limited.
[0049] In the present invention, the negative electrode material layer may further include a conductive agent. In the present invention, the conductive agent is not particularly limited as long as it achieves the object of the present invention, and may include, for example, at least one of the conductive agents described above, but is not limited thereto.
[0050] In the present invention, the negative electrode material layer may further include a binder. In the present invention, the binder is not particularly limited as long as it achieves the object of the present invention, and may include, for example, at least one of the binders described above, but is not limited thereto.
[0051] Optionally, the negative electrode may further include a conductive layer, and the conductive layer is located between the negative electrode current collector and the negative electrode material layer. In the present invention, the composition of the conductive layer is not particularly limited, and may be a conductive layer commonly used in the field, and the conductive layer may include, but is not limited to, the conductive agent and the binder.
[0052] In the present invention, the separator may be any material that achieves the object of the present invention, and is not particularly limited, and may include, for example, at least one of polyethylene (PE), polypropylene (PP), polytetrafluoroethylene-based polyolefin (PO)-based separators, polyester films (e.g., polyethylene terephthalate (PET) films), cellulose films, polyimide films (PI), polyamide films (PA), spandex, aramid films, woven films, nonwoven films (nonwoven fabrics), microporous films, composite films, separator films, laminate films, and spun films, but is not limited thereto, and is preferably PP. The separator of the present invention may have a porous structure, and the size of the pores may be any material that achieves the object of the present invention, and is not particularly limited, for example, 0.01 μm to 1 μm. In the present invention, the thickness of the separator may be any material that achieves the object of the present invention, and is not particularly limited, for example, 5 μm to 500 μm, preferably 25 μm.
[0053] For example, the separator may include a substrate layer and a surface treatment layer. The substrate layer may be a nonwoven fabric, a membrane, or a composite membrane with a porous structure, and the material of the substrate layer may include at least one of polyethylene, polypropylene, polyethylene terephthalate, polyimide, etc., but is not limited thereto. Optionally, a polypropylene porous membrane, a polyethylene porous membrane, a polypropylene nonwoven fabric, a polyethylene nonwoven fabric, or a polypropylene-polyethylene-polypropylene porous composite membrane may be used. Optionally, a surface treatment layer is provided on at least one surface of the substrate layer, and the surface treatment layer may be a polymer layer or an inorganic layer, or may be a mixed layer formed by mixing a polymer and an inorganic material.
[0054] The inorganic layer may include, but is not limited to, inorganic particles and a binder, and in the present invention, the inorganic particles are not particularly limited and may include, but are not limited to, at least one of alumina, silica, magnesia, titania, hafnia, tin oxide, ceria, nickel oxide, zinc oxide, calcium oxide, zirconium oxide, yttrium oxide, silicon carbide, boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide, and barium sulfate. In the present invention, the binder is not particularly limited and may include, but is not limited to, at least one of polyvinylidene fluoride, vinylidene fluoride-hexafluoropropylene copolymer, polyamide, polyacrylonitrile, polyacrylic acid ester, polyacrylic acid, polyacrylic acid salt, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene, and polyhexafluoropropylene. The polymer layer includes a polymer, and the polymer material may include, but is not limited to, at least one of polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyvinyl ether, polyvinylidene fluoride, and poly(vinylidene fluoride-hexafluoropropylene), and the like.
[0055] In the present invention, the electrolyte may further include a lithium salt, and the lithium salt may be any suitable salt that satisfies the purpose of the present invention, and may include, but is not limited to, at least one of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, LiSiF6, LiBOB, and lithium difluoroborate. Preferably, the lithium salt includes LiPF6.
[0056] In the present invention, the electrolyte may further include a non-aqueous solvent, and in the present invention, the non-aqueous solvent may be any solvent that can achieve the object of the present invention, and is not particularly limited thereto. For example, the non-aqueous solvent may include at least one of a carbonate compound, a carboxylate compound, an ether compound, and other organic solvents, but is not limited thereto. The carbonate compound may include at least one of a cyclic carbonate compound and / or a fluorocarbonate compound, but is not limited thereto. The cyclic carbonate may include at least one of ethylene carbonate (also called ethylene carbonate, abbreviated as EC), propylene carbonate (PC), butylene carbonate (BC), and vinyl ethylene carbonate (VEC), but is not limited thereto. The fluorocarbonate compound can include, but is not limited to, at least one of fluoroethylene carbonate (also called fluoroethylene carbonate, abbreviated as FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, and trifluoromethylethylene carbonate. The carboxylate compounds can include, but are not limited to, at least one of methyl formate, methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, gamma-butyrolactone, decanolide, valerolactone, mevalonolactone, and caprolactone.The ether compounds can include, but are not limited to, at least one of dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran, and tetrahydrofuran.The other organic solvent may include, but is not limited to, at least one of dimethylsulfoxide, 1,2-dioxolane, sulfolane, methylsulfolane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, formamide, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, trioctyl phosphate, and phosphate ester. The mass percentage of the non-aqueous solvent relative to the mass of the electrolyte solution may be 15% to 80%, for example, 15%, 20%, 30%, 40%, 50%, 60%, 70%, or 80%, or any range of the above values.
[0057] The electrochemical device of the present invention is not particularly limited and may include any device in which an electrochemical reaction occurs. In some embodiments, the electrochemical device includes, but is not limited to, a lithium metal secondary battery, a lithium ion secondary battery (lithium ion battery), a lithium polymer secondary battery, and a lithium ion polymer secondary battery.
[0058] The preparation process of the electrochemical device is well known to those skilled in the art, and the present invention is not particularly limited, and may include, for example, but is not limited to, the following steps: A positive electrode, a separator, and a negative electrode are stacked in order, and if necessary, the electrode assembly is wound or folded to obtain a wound structure electrode assembly, and the electrode assembly is placed in a packaging bag, and an electrolyte is injected into the packaging bag and sealed to obtain an electrochemical device. Alternatively, after stacking the positive electrode, the separator, and the negative electrode in order, the four corners of the entire stacked structure are fixed with tape to obtain a stacked structure electrode assembly, and the electrode assembly is placed in a packaging bag, and an electrolyte is injected into the packaging bag and sealed to obtain an electrochemical device. In addition, an overcurrent protection element, a lead plate, etc. may be placed in the packaging bag as necessary to prevent the internal pressure rise, overcharging and discharging, etc. of the electrochemical device.
[0059] The third aspect of the present invention provides an electronic device comprising the electrochemical device according to any of the above embodiments of the present invention.The electrochemical device provided by the present invention has good cycle and storage characteristics, and the positive electrode has a higher specific capacity.Therefore, the electronic device provided by the present invention has a longer service life and good characteristics.
[0060] The electronic device of the present invention is not particularly limited, and may be any known electronic device used in the prior art.In some embodiments, the electronic device includes, but is not limited to, notebook computers, pen-input computers, mobile computers, electronic book players, mobile phones, portable facsimiles, portable copy machines, portable printers, stereo headsets, video recorders, liquid crystal televisions, portable cleaners, portable CD players, mini discs, transceivers, electronic notebooks, calculators, memory cards, portable tape recorders, radios, backup power sources, motors, automobiles, motorcycles, auxiliary bicycles, bicycles, lighting equipment, toys, game machines, clocks, power tools, flashlights, cameras, large household storage batteries, and lithium ion capacitors.
[0061] The present invention provides a positive electrode active material containing Mn and Al elements, the positive electrode active material particles including a first region close to the surface of the positive electrode active material particles and a second region away from the surface of the positive electrode active material particles, where a1 is a molar ratio of Al / Mn in the first region and a2 is a molar ratio of Al / Mn in the second region, and a1 and a2 satisfy 1.1≦a1 / a2≦100. By adjusting the molar ratio a1 of Al / Mn in the first region and the ratio a1 / a2 between the molar ratio a1 of Al / Mn in the first region and the molar ratio a2 of Al / Mn in the second region within the above range, Al in the positive electrode active material is concentrated in the region close to the surface of the positive electrode active material, effectively improving the manganese elution phenomenon of the positive electrode and improving the cycle characteristics and storage characteristics of the electrochemical device, while at the same time reducing the total content of Al in the positive electrode active material, thereby maintaining a high specific capacity of the positive electrode, and improving the overall characteristics of the electrochemical device. [Brief description of the drawings]
[0062] In order to more clearly describe the technical solutions of the embodiments of the present invention, the following briefly describes the drawings that need to be used in the embodiments. The drawings described below are only some of the embodiments of the present invention, and it is obvious that those skilled in the art can obtain other embodiments based on these drawings.
[0063] [Figure 1] FIG. 1 is a schematic cross-sectional view of a positive electrode active material particle in some embodiments of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0064] In order to better clarify the objectives, technical solutions and advantages of the present invention, the present invention will be described in more detail below by taking embodiments with reference to the drawings. It is clear that the described embodiments are only some of the embodiments of the present invention, and not all of the embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention fall within the protection scope of the present invention.
[0065] 1 shows a schematic cross-sectional view of a positive electrode active material particle according to some embodiments of the present invention. As can be seen from the cross-sectional view, the first region 11 is a region close to the surface of the positive electrode active material 10 particle, and the second region 12 is a region away from the surface of the positive electrode active material 10 particle. In the embodiments of the present invention, the present invention will be described using a lithium ion battery as an example of an electrochemical device, but the electrochemical device of the present invention is not limited to a lithium ion battery.
[0066] Working Example Hereinafter, the embodiments of the present invention will be described in more detail with reference to examples and comparative examples. Various tests and evaluations are performed as follows. Unless otherwise specified, "%" is based on mass.
[0067] Measurement method and equipment: Elemental content determination: a) Prepare a sulfuric acid solution with a concentration of 2.4 mol / L. b) Take 50 g of positive electrode active material (fully discharge a lithium ion battery to 2.5 V, scrape off the positive electrode material layer on the positive electrode with a ceramic knife, and bake the positive electrode active material layer at 400 ° C for 5 hours to obtain the positive electrode active material). c) Mix 300 mL of sulfuric acid solution with 50 g of positive electrode active material, place on a magnetic stirrer and stir, fixing the stirring speed at 200 r / min; d) After 6 hours, the stirring is stopped and the mixture is left to stand, and after standing for 4 hours, the mixture is suction filtered through a filter paper, and the filtrate is taken and measured using an inductively coupled plasma emission spectrometer (model number: Thermo ICAP6300). The molar ratios between different elements in the first region, such as the molar ratio of Al / Mn, the molar ratio of Li / Mn, the molar ratio of Nb / Mn and the molar ratio of F / Mn, can be calculated and obtained; e) After suction filtration, the sample was dried at 85°C for 8 hours. f) The dried sample was measured using an inductively coupled plasma optical emission spectrometer (model: Thermo ICAP6300), and the molar ratios between different elements in the second region, such as the molar ratio of Al / Mn, the molar ratio of Li / Mn, the molar ratio of Nb / Mn, and the molar ratio of F / Mn, were calculated.
[0068] Mn 3+ / Mn 4+ Molar ratio determination: X-ray photoelectron spectroscopy (XPS) revealed that Mn in the first and second regions of the positive electrode active material 3+ / Mn 4+ The molar ratio was determined.
[0069] Measurement of cycle characteristics: At 25°C, a lithium-ion battery is charged at a constant current of 0.5C up to 4.2V, then charged at a constant voltage of 0.05C at 4.2V, and then discharged at a constant current of 1C down to 2.8V. The discharge capacity is D 01 According to the above operation steps, the lithium ion battery was subjected to a cycle process of "0.5C charge-1C discharge" multiple times, and 500 cycles were performed, and the discharge capacity after the 500th cycle was measured as D1. Capacity retention rate after 500 cycles at 25°C (%) = D1 / D01 ×100%.
[0070] Determination of storage properties: The lithium-ion battery was left to stand for 30 min in an environment of 25°C, then charged at a constant current of 0.2C to 4.2V, charged at a constant voltage of 4.2V to 0.05C, left to stand for 30 min, and then discharged at a rate of 0.5C to 2.8V. The discharge capacity at this time was recorded as the capacity of the lithium-ion battery before storage. The fully charged battery was then placed in an oven at about 60°C and stored for about 7 days, after which the capacity after storage was measured. The specific test process was as follows: The lithium-ion battery was left to stand for 30 min in an environment of 25°C, then charged at a constant current of 0.2C to 4.2V, charged at a constant voltage of 4.2V to 0.05C, left to stand for 30 min, and then discharged at a rate of 0.5C to 2.8V. The discharge capacity at this time was recorded as the capacity of the lithium-ion battery after storage. High temperature storage capacity retention rate at 60°C = capacity after storage / capacity before storage × 100%. For each Example or Comparative Example, four lithium ion batteries were measured, and the average value was used as the final result.
[0071] Measurement of specific capacitance: A button battery was manufactured using the positive electrode and lithium metal of the examples or comparative examples, and in an environment of 25°C, the button battery was charged at a constant current and constant voltage with a charging current of 0.5C (i.e., the current value at which the theoretical capacity is completely discharged for 2 hours) until the upper limit voltage of the button battery reached 4.2V, and then discharged at a constant current with a discharging current of 0.2C until the final voltage reached 2.8V, and the initial discharge capacity was recorded. The ratio of the initial discharge capacity to the mass of the positive electrode was recorded as the specific capacity of the positive electrode. For each example or comparative example, four positive electrodes were measured, and the average value was taken as the final result. Here, the mass of the positive electrode was the mass obtained by subtracting the mass of the positive electrode current collector. Here, the button battery was prepared using a preparation method known in the art, and the electrolyte in the button battery was the electrolyte used in each example or comparative example.
[0072] Measurement of separator heat generation start temperature: Measurement was performed using DSC, and a DSC curve of the separator was obtained at a temperature rise rate of 10° C. / min, and the heat generation initiation temperature of the separator was obtained from the DSC curve.
[0073] How to measure particle size: The particle size of the positive electrode active material or the negative electrode active material was measured using a laser particle sizer (model number: Mastersize3000). Dv10, Dv50, Dv90, and Dv99 were the diameters at which the cumulative volume was 10%, 50%, 90%, and 99% in the volume-based distribution of particles measured by a laser scattering particle sizer.
[0074] Example 1-1 <Preparation of Positive Electrode Active Material> Primary firing: The raw materials MnO2, Al2O3 and Li2CO3 are mixed so that the Al / Mn molar ratio is x1 and the Li / Mn molar ratio is y1, and fired at temperature T1 for firing time t1 to obtain an intermediate product. Secondary calcination: Al2O3, Li2CO3 and the intermediate product were further mixed and calcined at a temperature T2 for a calcination time t2 to obtain a positive electrode active material, which was lithium manganese oxide (LMO) containing Al element.
[0075] Here, the Al / Mn molar ratio of Al in Al2O3 added during secondary firing to Mn in the intermediate product was x2, the Li / Mn molar ratio of Li in Li2CO3 added during secondary firing to Mn in the intermediate product was y2, and the raw material MnO2 contained Al and had an Al / Mn molar ratio of x0. The positive electrode active material had Dv99 of 45 μm, Dv90 of 26 μm, Dv50 of 11.2 μm, and Dv10 of 6 μm.
[0076] <Preparation of positive electrode> The positive electrode active material prepared above, acetylene black as a conductive agent, and polyvinylidene fluoride as a binder were mixed in a mass ratio of 96.5:2:1.5, N-methylpyrrolidone (NMP) was added, and the mixture was uniformly stirred with a vacuum stirrer to obtain a positive electrode slurry, the solid content of which was 70 wt%. The positive electrode slurry was uniformly applied to one surface of an aluminum foil as a positive electrode current collector having a thickness of 12 μm, and the aluminum foil was dried at 120 ° C for 1 hour to obtain a positive electrode having a positive electrode material layer applied on one side. The above steps were repeated on the other side of the aluminum foil to obtain a positive electrode having a positive electrode material layer applied on both sides. Next, cold pressing, cutting, and slitting were performed, and the mixture was dried under vacuum conditions at 120 ° C for 1 hour to obtain a positive electrode having a size of 74 mm × 867 mm.
[0077] <Preparation of negative electrode> The negative electrode active material artificial graphite, the conductive agent acetylene black, the binder styrene butadiene rubber (SBR), and the thickener sodium carboxymethylcellulose (CMC) were mixed in a mass ratio of 95:2:2:1, deionized water was added, and the mixture was uniformly stirred with a vacuum stirrer to obtain a negative electrode slurry. The solid content of the negative electrode slurry was 75 wt%. The negative electrode slurry was uniformly applied to one side of a copper foil, which was a negative electrode current collector with a thickness of 12 μm, and the copper foil was dried at 120 ° C. to obtain a negative electrode with a coating layer thickness of 130 μm on one side coated with a negative electrode material layer. The above steps were repeated on the other side of the aluminum foil to obtain a negative electrode with a negative electrode material layer applied on both sides. Next, cold pressing, cutting, and slitting were performed, and the mixture was dried for 1 hour under vacuum conditions at 120 ° C. to obtain a negative electrode with a size of 78 mm x 875 mm. Here, the negative electrode material has a Dv99 of 30 μm, a Dv90 of 18 μm, a Dv10 of 5 μm, an OI value of 18, and a graphitization degree of 96%.
[0078] <Preparation of electrolyte> In a glove box under a dry argon atmosphere, EC, PC, DEC, and EMC were mixed in a mass ratio of 5:1:4:7 to obtain an organic solvent, and then lithium salt LiPF6 was added to the organic solvent, dissolved, and mixed uniformly to obtain an electrolyte solution, where the mass percentage of LiPF6 in the electrolyte solution was 12.5%, and the remainder was the organic solvent.
[0079] <Preparation of separator> A 7 μm-thick porous polyethylene thin film (manufactured by Celgard) was used, and the separator's heat generation starting temperature was 141°C.
[0080] <Preparation of lithium-ion batteries> The prepared positive electrode, separator, and negative electrode were stacked in this order, and the separator was placed between the positive electrode and the negative electrode to serve as an insulator, and then wound up to obtain an electrode assembly. The electrode assembly was placed in an aluminum plastic film packaging bag, dried, and then an electrolyte was injected. The lithium ion battery was obtained through processes such as vacuum packaging, standing, formation, and side cutting.
[0081] Examples 1-2 to 1-8 The same procedure as in Example 1-1 was carried out except that the preparation parameters were adjusted as shown in Table 1.
[0082] Examples 2-1 to 2-4 The same procedure as in Examples 1-4 was carried out except that the preparation parameters were adjusted as shown in Table 2.
[0083] Examples 3-1 to 3-5, 3-7 and 3-8 In <Preparation of positive electrode active material>, the compound corresponding to the M1 element added during primary firing and its content were adjusted to prepare a positive electrode active material with the molar ratio of each element shown in Table 3, except that the same procedure was followed as in Examples 1-4.
[0084] Examples 3-6 <Preparation of positive electrode active material> was carried out in the same manner as in Examples 1-4, except that in the primary firing, a compound corresponding to M1 element was added so that the M1 / Mn molar ratio was 1.0%, and in the secondary firing, a compound corresponding to M1 element was added so that the molar ratio of M1 to Mn in the intermediate product was 2.6%, to prepare a positive electrode active material having the molar ratios of each element shown in Table 3.
[0085] Examples 3-9 <Preparation of positive electrode active material> was carried out in the same manner as in Examples 1-4, except that in the primary firing, a compound corresponding to the M1 element was added so that the M1 / Mn molar ratio was 1.0%, and in the secondary firing, a compound corresponding to the M1 element was added so that the molar ratio of M1 to Mn in the intermediate product was 1.0%, to prepare a positive electrode active material having the molar ratios of each element shown in Table 3.
[0086] Examples 3-10 to 3-13 The same procedures as in Examples 1-4 were carried out except that a compound corresponding to M2 was added during the primary firing so that the mass percentage of the M2 element was the mass percentage shown in Table 3.
[0087] Examples 3-14 The same procedures as in Example 3-7 were carried out, except that a compound corresponding to M2 was added during the primary firing so that the mass percentage of the M2 element was the mass percentage shown in Table 3.
[0088] Example 4-1 to Example 4-3 The same procedure as in Examples 1-4 was carried out except that the preparation parameters were adjusted as shown in Table 4.
[0089] Examples 5-1 to 5-6 During the preparation of the electrolyte, the benzene-containing compound and PS were added according to Table 5, and the related preparation parameters were adjusted in the same manner as in Examples 1-4.
[0090] Comparative Example 1-1 and Comparative Example 1-2 The same procedure as in Examples 1-4 was carried out except that the preparation parameters were adjusted as shown in Table 1.
[0091] The relevant preparation parameters and property measurements for each of the Examples and Comparative Examples are as shown in Tables 1 to 5.
[0092] [Table 1]
[0093] From Examples 1-1 to 1-8 and Comparative Examples 1-1 to 1-2, it can be seen that if the ratio a1 / a2 between the molar ratio a1 of Al / Mn in the first region of the positive electrode active material and the molar ratio a2 of Al / Mn in the second region is within the range of the present invention, the specific capacity of the positive electrode in the electrochemical device, and the cycle characteristics and storage characteristics of the electrochemical device can be improved at the same time. At the same time, if the value of e is within the range of the present invention, the resulting electrochemical device has good cycle characteristics and storage characteristics at the same time, and the positive electrode in the electrochemical device also has a higher specific capacity. From Examples 1-1 to 1-8 and Comparative Example 1-1, it can be seen that if the molar ratio a1 of Al / Mn in the first region is within the range of the present invention, the resulting electrochemical device has good cycle characteristics and storage characteristics at the same time, and the positive electrode in the electrochemical device also has a high specific capacity. From Examples 1-1 to 1-8, it can be seen that when the Al / Mn molar ratio a2 in the second region and the Al / Mn molar ratio of the positive electrode active material are within the range of the present invention, the resulting electrochemical device simultaneously has good cycle characteristics and storage characteristics, and the positive electrode in the electrochemical device also has a high specific capacity.
[0094] [Table 2]
[0095] From Examples 1-4 and 2-1 to 2-4, it can be seen that when the ratio b1 / b2 of the molar ratio b1 of Li / Mn in the first region of the positive electrode active material to the molar ratio b2 of Li / Mn in the second region is within the range of the present invention, the resulting electrochemical device has good cycle characteristics and storage characteristics at the same time, and the positive electrode in the electrochemical device also has a high specific capacity. As the value of b1 / b2 increases, the cycle characteristics and storage characteristics of the electrochemical device tend to gradually improve.
[0096] [Table 3]
[0097] From Examples 1-4 and 3-1 to 3-14, it can be seen that the cycle characteristics and storage characteristics of the electrochemical device and the specific capacity of the positive electrode in the electrochemical device can be further improved by adding the M1 element and / or the M2 element. From Examples 3-1 to 3-9, it can be seen that by introducing the M1 element within the range of the present invention into the positive electrode active material and setting the values of the M1 / Mn molar ratio, the Al / M1 molar ratio, and c1 / c2 within the ranges of the present invention, the obtained electrochemical device has good cycle characteristics and storage characteristics at the same time, and the positive electrode in the electrochemical device also has a high specific capacity. From Examples 3-10 to 3-13, it can be seen that by introducing the M2 element within the range of the present invention into the positive electrode active material and setting the mass percentage of the M2 element and the value of d1 / d2 within the ranges of the present invention, the obtained electrochemical device has good cycle characteristics and storage characteristics at the same time, and the positive electrode in the electrochemical device also has a high specific capacity. From Examples 1-4 and 3-14, it can be seen that simultaneous introduction of the M1 element and the M2 element can further improve the cycle characteristics and storage characteristics of the electrochemical device, and the specific capacity of the positive electrode in the electrochemical device.
[0098] [Table 4]
[0099] In general, the particle size of the positive electrode active material affects the characteristics of the electrochemical device, such as cycle characteristics and storage characteristics. From Examples 1-4 and 4-1 to 4-3, it can be seen that when the values of Dv90, Dv10, Dv99-Dv90, and (Dv99-Dv10) / Dv50 of the positive electrode active material are within the ranges of the present invention, the resulting electrochemical device has good cycle characteristics and storage characteristics at the same time, and the positive electrode in the electrochemical device also has a high specific capacity.
[0100] [Table 5]
[0101] In general, the type and content of components in the electrolyte of an electrochemical device affect the characteristics of the electrochemical device, such as cycle characteristics and storage characteristics. From Examples 1-4, 5-1 to 5-3, it can be seen that when the electrolyte contains a benzene-containing compound and the type and mass percentage are within the range of the present invention, the resulting electrochemical device has better cycle characteristics and storage characteristics at the same time. From Examples 1-4, 5-4 and 5-5, it can be seen that when the electrolyte contains PS and the mass percentage is within the range of the present invention, the resulting electrochemical device has better cycle characteristics and storage characteristics at the same time. From Examples 1-4 and 5-6, it can be seen that the benzene-containing compound and PS have a good additive effect, which can further improve the cycle characteristics and storage characteristics of the electrochemical device.
[0102] The above description is only a preferred embodiment of the present invention, and is not intended to limit the present invention. Any amendments, equivalent replacements, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention. [Explanation of symbols]
[0103] 10 positive electrode active material, 11 first region, 12 second region.
Claims
1. Contains Mn and Al elements, the positive electrode active material particle includes a first region close to a surface of the positive electrode active material particle and a second region remote from the surface of the positive electrode active material particle, a1 and a2 satisfy 1.1≦a1 / a2≦100, where a1 is a molar ratio of Al / Mn in the first region and a2 is a molar ratio of Al / Mn in the second region.
2. 2. The positive electrode active material according to claim 1, wherein a1 is 1% to 30% and / or a2 is 0.05% to 5%.
3. 2. The positive electrode active material according to claim 1, wherein the Al content in the first region is 0.01% to 0.5% by mass with respect to the mass of the positive electrode active material.
4. The positive electrode active material according to claim 1 , wherein the positive electrode active material is selected from lithium manganates containing Al element.
5. (a) the molar ratio of Al / Mn in the positive electrode active material is 0.1% to 10%; (b) Mn element is Mn 3+ and Mn 4+ and Mn in the second region. 3+ / Mn 4+ The molar ratio of Mn in the first region to 3+ / Mn 4+ When the molar ratio of the above is e, e is 0.80 to 0.95; (c) the positive electrode active material contains Li, and when a molar ratio of Li / Mn in the first region is b1 and a molar ratio of Li / Mn in the second region is b2, b1 and b2 satisfy 1≦b1 / b2≦2; The positive electrode active material according to claim 1 , which satisfies at least one of the following conditions.
6. The alloy further includes an M1 element, the M1 element including at least one of Ni, Co, Nb, Mo, V, W, Zr, Mg, Ti, La, Y, and B elements; The positive electrode active material is (d) the molar ratio of M1 / Mn is 0.1% to 5%; (e) the molar ratio of Al / M1 is 1 to 10; The positive electrode active material according to claim 1 , which satisfies at least one of the following conditions.
7. Further comprising an M2 element, the M2 element comprising F and / or S; The positive electrode active material according to claim 1, wherein the M2 element is present in an amount of 0.1% to 2% by mass based on the mass of the positive electrode active material.
8. The M2 element includes an F element, 8. The positive electrode active material according to claim 7, wherein, when a molar ratio of F / Mn in the first region is d1 and a molar ratio of F / Mn in the second region is d2, d1 and d2 satisfy 3≦d1 / d2≦50.
9. Further containing Nb element, 2. The positive electrode active material according to claim 1, wherein, when a molar ratio of Nb / Mn in the first region is c1 and a molar ratio of Nb / Mn in the second region is c2, c1 and c2 satisfy 3≦c1 / c2≦50.
10. The positive electrode active material has a Dv99 of 15 μm to 50 μm; The particle size of the positive electrode active material is (i) Dv90 and Dv99 satisfy 5 μm≦Dv90≦30 μm and 5 μm≦Dv99-Dv90≦21 μm; (ii) Dv10, Dv50 and Dv99 satisfy 2 μm≦Dv10≦10 μm and 1≦(Dv99-Dv10) / Dv50≦4; The positive electrode active material according to claim 1 , which satisfies at least one of the following conditions.
11. (f) a1 and a2 satisfy 5≦a1 / a2≦90; (g) the a1 is 5% to 30%; (h) the molar ratio of Al / Mn in the positive electrode active material is 2% to 10%; (i) b1 and b2 satisfy 1.1≦b1 / b2≦2; (j) d1 and d2 satisfy 3≦d1 / d2≦25; (k) the positive electrode active material has a Dv99 of 25 μm to 35 μm; (l) the particle size of the positive electrode active material satisfies 8 μm≦Dv99−Dv90≦12 μm; (m) the particle size of the positive electrode active material satisfies 4 μm≦Dv10≦7 μm and 2≦(Dv99−Dv10) / Dv50≦3; The positive electrode active material according to any one of claims 1 to 10, which satisfies at least one of the above.
12. A positive electrode, a negative electrode, and an electrolyte solution, The positive electrode comprises the positive electrode active material according to any one of claims 1 to 11, the positive electrode includes a positive electrode material layer and a positive electrode current collector; the positive electrode material layer includes a first positive electrode material layer and a second positive electrode material layer, the first positive electrode material layer is located between the second positive electrode material layer and the positive electrode current collector, the first positive electrode material layer has a greater Mn element content than the second positive electrode material layer.
13. Relative to the mass of the electrolyte, the electrolyte (iii) the electrolytic solution contains a chain carbonate, the chain carbonate is present in a mass percentage of 20% to 60%, and the chain carbonate contains at least one of dimethyl carbonate, diethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, and ethyl methyl carbonate; (iv) the electrolytic solution contains a benzene-containing compound, the benzene-containing compound is present in a mass percentage of 0.01% to 5%, and the benzene-containing compound contains at least one of biphenyl, fluorobenzene, and cyclohexylbenzene; (v) the electrolyte contains polystyrene, and the polystyrene is present in a mass percentage of 0.01% to 5%; 13. The electrochemical device according to claim 12, which satisfies at least one of the following conditions.
14. (x) the benzene-containing compound is present in an amount of 1% to 3% by mass relative to the mass of the electrolyte; (xi) the polystyrene is present in an amount of 0.01% to 3% by mass relative to the mass of the electrolyte; The electrochemical device according to claim 13 , wherein at least one of the following is satisfied:
15. the negative electrode includes a negative electrode material layer, the negative electrode material layer includes a negative electrode active material, the negative electrode active material includes at least one of natural graphite, artificial graphite, and hard carbon; The electrochemical device comprises: (vi) the negative electrode active material has a Dv10 satisfying 2 μm≦Dv10≦10 μm; (vii) the Dv90 and Dv99 of the negative electrode active material satisfy 5 μm≦Dv90≦20 μm and 5 μm≦Dv99−Dv90≦25 μm; (viii) the negative electrode active material has an orientation index value of 5 to 30; (ix) the degree of graphitization of the negative electrode active material is 92% to 96%; 13. The electrochemical device according to claim 12, which satisfies at least one of the following conditions.
16. The electrochemical device includes a separator; 13. The electrochemical device according to claim 12, wherein the separator has an exothermic onset temperature of 138° C. to 145° C. as measured by differential scanning calorimetry.
17. An electronic device comprising an electrochemical device according to any one of claims 12 to 16.
Citation Information
Patent Citations
Lithium-manganese-aluminum oxygen anode material and preparation method thereof
CN102683667A
Cathode active material, cathode and lithium battery including cathode active material, and method of preparing the cathode active material
CN103915610A
Preparation method for positive electrode material of lithium ion battery
CN106935803A
Alumina dry-coated cathode material precursor
JP2013539169A